Nonradical treatment is as effective as radical surgery in the management of cervical cancer stage IA1. Issue 5 (1st August 2002) - Nam, J.-H.; Kim, S.-H.; Kim, J.-H.; Kim, Y.-M.; Kim, Y.-T.; Mok, J.-E.
Abstract : This study was designed to evaluate a series of patients who underwent surgical management due to cervical cancer stage IA1 fitting the 1995 FIGO definition. A total of 149 patients were followed from 3 years to 11.7 years with a median follow-up interval of 5 years. The cases with invasions of ≤ 1 mm and > 1 mm but ≤ 3 mm were noted in 89 (59.7%) and 60 (41.3%) patients, respectively. Lymphvascular space invasion was identified in five patients. In 49 patients, conization or nonradical hysterectomy was performed without pelvic lymph node dissection (PLND) and pelvic recurrence developed in one patient who had an extended hysterectomy. PLND was performed in 100 patients and the average number of lymph nodes examined per case was 26.5 ± 10.1. None of the 100 patients had metastasis to the pelvic lymph node and recurrence. None of the 149 patients has died from recurrent disease. In conclusion, this study suggests that patients with cervical cancer stage IA1 have an extremely low risk of pelvic lymph node metastasis, very rarely recur, and present an excellent prognosis, so nonradical management that excludes PLND could be as effective as radical surgery in these patients.